Utilizing Musharakah Contracts in Indonesian Islamic Banks for InfrastructureFinancing - Mohamad Torik Langlang Buana; Amrizal; Nuradli Ridzwan Shah Moch Dali; Taufik Akbar (Accounting Study Program, Faculty of Economics and Business, Universitas Ahmad Dahlan, 2024)
Vol. 10 No. 2